2021
DOI: 10.1371/journal.pone.0254943
|View full text |Cite
|
Sign up to set email alerts
|

The influence of LncRNA H19 polymorphic variants on susceptibility to cancer: A systematic review and updated meta-analysis of 28 case-control studies

Abstract: Objective Although myriad researches upon the associations between LncRNA H19 polymorphic variants (rs2839698 G>A, rs217727 G>A, rs2107425 C>T, rs2735971 A>G and rs3024270 C>G) and the susceptibility to cancer have been conducted, these results remained contradictory and perplexing. Basing on that, a systematic review and updated meta-analysis was performed to anticipate a fairly precise assessment about such associations. Methods We retrieved the electronic databases EMBASE, PubMed and Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
1
5
2
Order By: Relevance
“…Our combined studies demonstrated a clear increase in cancer risk associated with H19 rs2839698 polymorphism in the overall and Asian population group, which contradicts the results of Wang et al (2021) and Liu et al (2020b) found no association between the H19 rs2839698 polymorphism and cancer risk neither in the overall group nor in the ethnicity subgroup. The obvious alteration of estimates of effect could be due to increased sample size, given that the 13 newly included studies accounted for 27.18% of individuals.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our combined studies demonstrated a clear increase in cancer risk associated with H19 rs2839698 polymorphism in the overall and Asian population group, which contradicts the results of Wang et al (2021) and Liu et al (2020b) found no association between the H19 rs2839698 polymorphism and cancer risk neither in the overall group nor in the ethnicity subgroup. The obvious alteration of estimates of effect could be due to increased sample size, given that the 13 newly included studies accounted for 27.18% of individuals.…”
Section: Discussioncontrasting
confidence: 99%
“… Liu et al (2020b) found that rs217727 is associated with increased cancer risk in the overall and Asian populations. However, our updated meta-analysis is more supportive of Wang’s study that no effect was detected between rs217727 polymorphism and cancer susceptibility in the general population and ethnicity subgroup ( Wang et al, 2021 ). This difference may result from 18 new articles included in our study.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations